2018
DOI: 10.1002/bdd.2118
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gene expression in vitamin D‐deficiency: Down‐regulation of liver Cyp7a1 and renal Oat3 in mice

Abstract: The vitamin D-deficient model, established in the C57BL/6 mouse after 8 weeks of feeding vitamin D-deficient diets in the absence or presence of added calcium, was found associated with elevated levels of plasma parathyroid hormone (PTH) and plasma and liver cholesterol, and a reduction in cholesterol 7α-hydroxylase (Cyp7a1, rate-limiting enzyme for cholesterol metabolism) and renal Oat3 mRNA/protein expression levels. However, there was no change in plasma calcium and phosphate levels. Appraisal of the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 78 publications
0
18
1
Order By: Relevance
“…It is long understood that vitamin D maintains bone health, due to its role in the maintenance of calcium homeostasis. Furthermore, in order to maintain a complete deficiency of vitamin D, we used a diet low in calcium, which has been shown not to affect serum calcium levels . While mice with experimental periodontitis that were injected with 25(OH)D 3 showed decreased bone loss, as do CYP27B1 −/− mice, our experiments are the first to demonstrate that a dietary deficiency in vitamin D leads to inflammation and alveolar bone loss.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is long understood that vitamin D maintains bone health, due to its role in the maintenance of calcium homeostasis. Furthermore, in order to maintain a complete deficiency of vitamin D, we used a diet low in calcium, which has been shown not to affect serum calcium levels . While mice with experimental periodontitis that were injected with 25(OH)D 3 showed decreased bone loss, as do CYP27B1 −/− mice, our experiments are the first to demonstrate that a dietary deficiency in vitamin D leads to inflammation and alveolar bone loss.…”
Section: Discussionmentioning
confidence: 87%
“…Serum samples from the mice at the end of 6 weeks showed that the mice fed a vitamin D‐absent diet exhibited very low levels of 25(OH)D 3 (Figure A). While this diet includes reduced calcium as well, this has been shown to lead to no reduction in serum calcium levels, even up to 8 weeks . Longer depletion of vitamin D would compromise the general health of the mice, potentially confounding the model .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of exogenously administered calcitriol has been investigated in mice (Chow et al, 2013; Quach et al, 2018), rats (Kissmeyer & Binderup, 1991; Paulson & Kenny, 1985), and humans under normal conditions (Bianchi et al, 1999; Brandi, Egfjord, & Olgaard, 2002; Gray et al, 1978; Seeman et al, 1980), and among patients with chronic kidney disease (CKD) (Ardissino et al, 2000; Brandi et al, 2002; Levine & Song, 1996; Salusky et al, 1990; Torregrosa, Campistol, Mas, Montesinos, & Martinez de Osaba, 1996) or cancer (Fakih et al, 2007; Muindi et al, 2009). Exogenously injected calcitriol would trigger changes in CYP27B1 and CYP24A1 enzymes as well as increase calcium absorption via the intestinal calcium channel, TRPV6 (den Dekker et al, 2003; Hoenderop et al, 2001; Meyer et al, 2006; Weber et al, 2001), giving rise to hypercalcemia (Laubenthal et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The role of VDR in cholesterol metabolism was implicated in mice in vivo ; serum cholesterol levels were slightly, but significantly, elevated in Vdr‐knockout mice (Wang et al, 2009) and vitamin D deficient mice (Quach et al, 2018). The regulatory mechanism of VDR on lowering cholesterol was elucidated by Chow et al (2014) who showed that activated Vdr upregulated liver Cyp7a1 (the rate‐limiting enzyme catabolizing cholesterol to bile acids) in mice by repressing the murine small heterodimer partner (Shp), a negative repressor of Cyp7a1 (Goodwin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%